Perilaku Makan dan Konsumsi Tablet Tambah Darah pada Siswi di SMKN 1 Kendari - Hartati Bahar (Jurnal Kendari Kesehatan Masyarakat, 2024)
Anemia is a health problem that is often found in society. Riskesdas data in 2018 shows that 26.8% of children aged 5-14 years suffer from anemia and as many as 32% in the 15-24 year age range. Consuming blood supplement tablets is one of the government's efforts to prevent anemia in young women. Objective: This study aims to determine the description of eating behavior and consumption of blood supplement tablets is among female students at SMK Negeri 01 Kendari. Method: This type of research is descriptive with a population of 42 class XI female students with a total research sample of 30 female students. Results: The results of this study show that there are 4 respondents who have a frequency of eating less than 3 times a day (13.3%), there are 6 female students who have dietary restrictions (20%), the consumption behavior of blood supplement tablets is only 2 people who regularly consume blood supplement tablets (6.7%) and the remaining 28 female students (93.3%) did not regularly consume blood supplement tablets for various reasons. Conclusion: Adolescent girls' compliance with consuming blood supplement tablets is still very poor so continuous education needs to be provided to change perceptions and increase motivation in consuming blood supplement tablets